Board attributes and herding in corporate investment: evidence from Chinese-listed firms. Issue 4 (2nd May 2016) - Bo, Hong; Li, Tao; Sun, Yanmei
Abstract : We examine whether board attributes, including board age, gender diversity, board independence, CEO duality, and board size, explain investment herding by using a panel of 1155 Chinese-listed non-financial firms during 1999–2004. Investment herding is measured by the absolute value of the difference between the investment ratio of firm i in year t and the average investment ratio of other firms in the same industry excluding firm i in year ( t −1). We find that corporate boards that have more young directors, more female directors, more independent directors, a CEO who is not the chairman of the board, and a larger board are more likely to make investment decisions closer to their peers in the same industry. We also provide evidence that investment herding is positively related to firm performance, suggesting that investment herding does not necessarily hurt shareholders in the Chinese context. We identify that herding in making investment decisions is a possible channel through which some board attributes, such as board age diversity, gender diversity, and board independence, contribute to firm performance.